A case of Menetrier's disease without Helicobacter pylori or hypoalbuminemia. (2015) - Azer, Mina; Sultan, Ahmad; Zalata, Khaled; Abd El-Haleem, Ibrahim; Hassan, Adel; El-Ebeidy, Gamal
Highlights: Menetrier's disease is a rare premalignant hypertrophic gastropathy. We describe a case of Menetrier's disease with an unusual presentation, without Helicobacter pylori or hypoalbuminemia. Menetrier's disease should be suspected in cases of upper GIT symptoms and hypertrophied gastric mucosa with or without Helicobacter pylori or hypoalbuminemia. Surgical management is a good option when medical treatment fails to relieve the symptoms and erase the risk of malignancy. Abstract: Introduction: Menetrier's disease is a rare premalignant hypertrophic gastropathy. It is characterized by huge gastric mucosal folds, peripheral edema due to protein loss and upper GIT symptoms such as epigastric pain, discomfort, nausea and vomiting. Presentation of case: Female patient 35 years old complaining of severe epigastric pain, dyspepsia, nausea and vomiting for 1 year. Upper GIT endoscopy and CT scan revealed thickening of gastric mucosa. Endoscopic biopsy was non-specific but showed moderate grade dysplasia and no Helicobacter pylori infection. All laboratory investigations were within normal including serum albumin. She underwent total gastrectomy with marked postoperative improvement of symptoms after recovery. Postoperative pathology revealed gastric fovular hyperplasia and glandular atrophy which are diagnostic for Menetrier's disease. Discussion: the preoperative diagnosis of Menetrier's disease in this case was challenged by its unusual features. There were neither H. pylori nor hypoalbuminemia. Literature review showed similarcases which can raise the suspicion of the presence of an undescribed subtype of the disease. Conclusion: Menetrier's disease should be suspected in cases of upper GIT symptoms and hypertrophied gastric mucosa with or without H. pylori or hypoalbuminemia. The preoperative diagnosis could not be confirmed unless a whole mucosal thickness biopsy is performed. Surgical management is a good option when medical treatment fails to relieve the symptoms and erase the risk of malignancy.